1980
DOI: 10.1161/01.res.47.4.578
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of rat arterial smooth muscle cell proliferation by heparin. II. In vitro studies.

Abstract: We studied in vitro the effects heparin on the growth of rat aortic smooth muscle cells. Measurements of growth were monitored by [3H]thymidine uptake and changes in cell number over a period of 3 days. Our results show that heparin-highly anticoagulant or nonanticoagulant-significantly inhibits growth of smooth muscle cells. We also show that this is a highly specfic interaction with regard to molecule and cell type: i.e., other polyanions, except for a low molecular weight dextran sulfate, do not have the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
162
0
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 325 publications
(172 citation statements)
references
References 19 publications
9
162
0
1
Order By: Relevance
“…The negative charge of HA does not seem to be the sole factor responsible for its inhibitory effect, since chondroitin sulfate and dextran sulfate, which are more highly charged than HA, were ineffective. Heparin and heparan sulfate have been shown to inhibit proliferation of a variety of cell types (47)(48)(49)(50). In contrast to the inhibitory effect of HA described herein, the effect of heparin on smooth muscle cell proliferation is apparently mediated by specific cell surface receptors that recognize small oligosaccharides derived from heparin (51).…”
Section: Discussionmentioning
confidence: 72%
“…The negative charge of HA does not seem to be the sole factor responsible for its inhibitory effect, since chondroitin sulfate and dextran sulfate, which are more highly charged than HA, were ineffective. Heparin and heparan sulfate have been shown to inhibit proliferation of a variety of cell types (47)(48)(49)(50). In contrast to the inhibitory effect of HA described herein, the effect of heparin on smooth muscle cell proliferation is apparently mediated by specific cell surface receptors that recognize small oligosaccharides derived from heparin (51).…”
Section: Discussionmentioning
confidence: 72%
“…vations made in our laboratory over the past several years, which demonstrate that heparin inhibited the growth of SMC in vivo and in vitro (Clowes and Karuovsky, 1977;Guyton et al, 1980;Hoover et al, 1980;Castellot et at., 1981). In our previous structure-function studies (Castellot et al, 1984), we used heparin fragments and chemically modified commercial heparin to determine that the smallest antiproliferative fragment was a hexasaccharide, and that both N-and O-sulfates were important for maintaining the growth inhibitory capacity of heparin.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier work from our laboratory demonstrated that heparin inhibited the proliferation of SMC in vivo and in vitro (Clowes and Karnovsky, 1977;Guyton et al, 1980;Hoover et al, 1980;Castellot et al, 1981). Both anticoagulant and non-anticoagulant heparin species were equally effective as SMC antiproliferative agents.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…Azizkhan et al (1980) first reported that heparin induced expression of angiogenic substances in mast cells. Hoover et al (1980) subsequently demonstrated that heparin stimulated the growth of bovine aortic endothelial cells in vitro, but heparin was also demonstrated to inhibit the proliferation of fibroblasts and SMC. Potential biological roles of heparin in the process of angiogenesis has been mainly examined in relation to other growth factors, such as acidic fibroblast growth factor (aFGF) (Mueller et al 1989;Jesundason et al 2000), basic fibroblast growth factor (bFGF) (Yamashita et al 1992;Toriyama et al 1997) and vascular endothelial growth factor (VEGF) (Heaky et al 2000;Norrby 2000).…”
Section: Discussionmentioning
confidence: 99%